A case study on implementing lean ergonomic manufacturing systems (LEMS) in an automobile industry. (September 2016) - Srinivasa Rao, P; Niraj, Malay
Abstract: Lean manufacturing is a business strategy developed in Japan. In the present scenario, the global market is developing new techniques for getting more and more production rate with a good quality under low cost. In this context, human factors have to be given importance to their working conditions. The study demonstrates the adoption of ergonomic conditions in lean manufacturing for the improvement of organizational performance of the industry. The aim of ergonomics is to adapt the new techniques to their work in efficient and safe ways in order to optimize the human health conditions and increasing the production rate. By conducting survey on various disciplines and showed how the production rate and human ergonomic conditions is affected.